Nutrition and Foods for Skin Health - Gülsüm Akalın; Zeliha Selamoglu (Research Center for Rational Use of Drugs (RCRUD), 2019)
This review reports the importance of the natural foods and nutritional status in the maintenance of healthy skin. The weaknesses in nutritional status that convert skin structure and function might also directly affect skin appearance. Thus, it needs to investigation the effects of micronutrients and various natural agents that are important for skin health.